The effect of the perception of financial risk on intention to use digital payment platforms - Longgy, Dodhy Hyronimus Ama; Alrawahna, Ammar; Tamin, Masran; Awotkay, Apolinaris Sapuk; Siamsa, Simon (Ifma Publishing, 2024)
The aims of this research are to identify the factors shaping consumers' financial risk perceptions regarding the use of digital payment platforms and to analyze the relationship between financial risk perceptions and consumers' intentions to use digital payment platforms in Merauke Regency. This study employs a qualitative approach. The subjects consist of consumers who currently use or are potential users of digital payment platforms, local business actors offering digital payment options to consumers, and local economic observers or experts familiar with the economic and cultural contexts of Merauke Regency. Thematic analysis is used to identify the main themes from data collected through interviews and observations, supplemented by narrative analysis to construct the stories and experiences of the research subjects. The findings indicate that financial risk perceptions, particularly concerns about financial loss and fraud, remain significant barriers to the widespread adoption of digital payment platforms in Merauke Regency. The study also highlights that consumers’ intentions to use digital payment platforms are influenced by their financial risk perceptions and awareness of practical benefits, which can be strengthened through educational efforts and increased financial literacy.